Exploring a COVID‐19 Endemic Scenario: High‐Resolution Agent‐Based Modeling of Multiple Variants (Adv. Theory Simul. 1/2023). Issue 1 (10th January 2023) - Truszkowska, Agnieszka; Zino, Lorenzo; Butail, Sachit; Caroppo, Emanuele; Jiang, Zhong‐Ping; Rizzo, Alessandro; Porfiri, Maurizio
Abstract : Exploring a COVID‐19 Endemic Scenario In article 2200481, Agnieszka Truszkowska, Maurizio Porfiri and co‐workers discuss the implications of the concurrent spread of two COVID‐19 strains in the model town of New Rochelle, NY, building upon their previously published high‐resolution agent‐based model. Image by Anna Sawulska, Alain Boldini, and Maurizio Porfiri.